Pregnancy outcomes in anti-NMDA receptor encephalitis: Case series. Issue 3 (May 2020) - Joubert, Bastien; García-Serra, Anna; Planagumà, Jesús; Martínez-Hernandez, Eugenia; Kraft, Andrea; Palm, Frederick; Iizuka, Takahiro; Honnorat, Jérôme; Leypoldt, Frank; Graus, Francesc; Dalmau, Josep
Abstract : Objective: To report the effects of anti-NMDA receptor (NMDAR) encephalitis in pregnant patients and their babies. Methods: We studied a retrospective cohort of patients who developed anti-NMDAR encephalitis during pregnancy or became pregnant while recovering from the encephalitis. In addition, we reviewed the English literature between 2010 and 2019 related to this topic. Results: We studied 11 patients; 6 developed anti-NMDAR encephalitis during pregnancy, and 5 became pregnant while recovering. There were no obstetrical complications, but 6 (55%) babies were premature. Ten newborns were healthy, and 1 (9%) developed transient respiratory distress. Nine infants had assessable follow-up (median 18 months; range, 7–96 months), and all showed normal development. We identified 21 cases in the English literature. Obstetrical complications occurred in 7 (33%) pregnancies. Two patients died of septic shock (1 baby successfully delivered), another 2 had miscarriages, and in 2, the pregnancy was terminated. Sixteen babies (76%) were delivered, 9 (56%) premature. At birth, 13/16 (81%) newborns were healthy, 2/16 (13%) had transient neurologic or respiratory symptoms, and 1 (6%) died of brain edema. Follow-up (median 12 months; range, 6–36 months) was reported for 8 children: 7 (88%) showed normal development and behavior, and 1 (13%) cortical dysplasia. Immunotherapy was used during pregnancy in 7 (64%) of our patients and 18 (86%) of the reported cases, including rituximab in 4 cases, without adverse effects. Conclusions: Patients who develop anti-NMDAR encephalitis during pregnancy or become pregnant during recovery often have obstetrical complications, but most of the newborns are healthy and appear to have normal development.